2019
DOI: 10.1007/s00432-019-03037-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in serous ovarian cancer is not associated with LATS expression

Abstract: BackgroundLarge tumor suppressor (LATS) proteins are putative tumor suppressors and poorly expressed associated with poor outcome in many cancers. A recent immunohistochemistry study showed that LATS protein expression correlated with poor outcome in serous ovarian cancer.Materials and methodsWe analyzed LATS expression in various ovarian cancer transcriptomic data sets and immunohistochemically assessed LATS protein expression in a Swiss ovarian tumor cohort. Results were compared to clinicopathological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Epigenetic alteration often leads to dysregulated gene expression. LATS2 is one of the Hippo members, 33 and low LATS2 was associated with better survival in OC 34 . E‐cadherin is one of epithelial‐mesenchymal transformation markers and increased E‐cadherin inhibits cell invasion of OC 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic alteration often leads to dysregulated gene expression. LATS2 is one of the Hippo members, 33 and low LATS2 was associated with better survival in OC 34 . E‐cadherin is one of epithelial‐mesenchymal transformation markers and increased E‐cadherin inhibits cell invasion of OC 35 .…”
Section: Discussionmentioning
confidence: 99%
“…High-grade serous ovarian cancer (HGSOC) is the most common, aggressive, and fatal type of ovarian cancer. Almost 30% of patients died within ve years of diagnosis (7), mainly because of lack of disease-speci c symptoms, prominent biomarkers, and effective therapy or targeted drugs (8)(9)(10). Despite sharing some similar histological characters and terminology, high-and low-grade SOCs are now acknowledged as two different neoplasms (11).…”
Section: Introductionmentioning
confidence: 99%
“…It was also proved that ARHGAP5 could be a prognostic marker of gastric cancer [50] and the expression level of it was associated with invasive and migrative ability of nasopharyngeal carcinoma cells [51]. LATS1 is one of family proteins of large tumor suppressor (LATS) and has been proposed to be a tumor suppressor [52]. It had been found that the expression level of LATS1 had decreased in serous ovarian cancer patients but this gene highly expressed in normal ovarian tissue [52,53].…”
Section: Discussionmentioning
confidence: 98%
“…LATS1 is one of family proteins of large tumor suppressor (LATS) and has been proposed to be a tumor suppressor [52]. It had been found that the expression level of LATS1 had decreased in serous ovarian cancer patients but this gene highly expressed in normal ovarian tissue [52,53]. SLC34A2 was proved to have an evident effect in the progression of several types of cancers, such as in ovarian cancer [54,55], breast cancer and non-small cell lung cancer [56,57].…”
Section: Discussionmentioning
confidence: 99%